Characteristic Acoustic Emission Sequences of Rock Samples Under Uniaxial Loading - Nic Slatalla (International Conference on Ground Control in Mining, 2008)
Acoustic emission monitoring techniques are a powerful tool for analysing deformation behaviour and fracture characteristics of rock samples under uniaxial loading. Uniaxial compression tests were carried out on three different types of sandstone for a better understanding of acoustic emission response with respect to rock deformation and damage develop-ment. All sandstone samples revealed congruent characteristic acous-tic emission patterns which correlated directly with distinct stress-strain stages. However, the acoustic response and development within the individual stages proved to be entirely different due to variations in their microstructure.